Special Career Decisions and Some Interventions Required for the Development of Decision Making - Fazaria Muslimah (Indonesian Journal of Cultural and Community Development, 2019)
The purpose of this study is to assist individuals in understanding themselves with the given career interventions. Career decisions are the ability of a person to use his knowledge, emotions and thoughts. The ability of career decisions is based on cognitive, affective and psychomotor aspects. Cognitive aspects; understand themselves and the environment (family, friends and society), knowledge of decision making steps, understanding of information. Affective aspects; responsible, emotionally involved in discussions about careers. Psychomotor aspects; use of knowledge and thought. Career decisions can be made with a variety of career interventions in accordance with the objectives to be achieved with several alternative options in developing career decisions. To develop career decisions some appropriate interventions are given such as reality counseling, cognitive reconstruction and social cognitive models.